Negligence as a condition of civil liability of health care institutions - Ye. Ye. Vasilyeva (Бюллетень сибирской медицины)
In this article a significance of a negligence of health care institutions when bringing them to civil liability has been investigated. A common rule of assignment of responsibility only when guilty has been examined as well as an exclusion of responsibility in case of increased (guiltless) liability. Examples have been given and a legal treatment of situations when a mutual contributory negligence took place (executor’s negligence as well as recipient’s (patient’s) negligence) has been presented. The significance of presumption of innocence in civil law has been revealed.